The Reliability and Validity of a Novel Clinical Test for Assessing Shoulder Rotation ROM in Collegiate Baseball Players: Functional Assessment of System Tension of the Shoulder (FAST-SHDR) - Steven Dischiavi; Jesse Perry; Connor Burk; Jeremy Chiang; Chris Bleakley (International Journal of Sports Physical Therapy)
# Background